Soluble and transparent polyimides with high Tg from a new diamine containing tert‐butyl and fluorene units. Issue 7 (26th October 2015) - Yi, Lang; Li, Congyan; Huang, Wei; Yan, Deyue
ABSTRACT: A novel diamine monomer1, 4, 4'‐(9 H ‐fluorene‐9, 9‐diyl)‐bis(2‐ tert ‐butylaniline), was synthesized from 9‐fluorenone and 2‐ tert ‐butylaniline by the condensation reaction. Then it was polymerized with several commercial aromatic dianhydrides, respectively, to produce polyimides (PIs) by the one‐pot method. The number‐averaged molecular weights of the resulting PIs are in the range of (4.54–8.82) × 10 4 with polydispersity indices from 2.51 to 4.33 by gel permeation chromatography measurement. They are soluble in many organic solvents and can form transparent and tough films by solution‐casting. The cut‐off wavelengths of UV–vis absorption for the PI films are below 360 nm, which are much lower than that of Kapton film. The light transparency of them is above 90% in the visible light range from 400 to 760 nm. They also display relatively low dielectric constants (from 2.79 to 3.00), low water absorption rates (<1%), and high tensile strength (> 50 MPa). Their excellent solubility and transparency can be attributed to the incorporation of tert ‐butyl groups and fluorene units into the rigid backbones of PIs. Simultaneously, they still maintain the high thermal stability (the 5% weight loss temperature in the range from 526 to 539 °C in nitrogen) and the high glass transition temperatures ( T g  > 340 °C). © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 976–984 Abstract : A series of soluble polyimides (PIs) containing large pendant groups with tert ‐butyl and fluorene units were synthesized through a one‐pot method. The introduction of tert ‐butyl and fluorene units evidently enhanced the transparency of the PI films and lightened their color. All the resulting PIs exhibited high T g, excellent thermal stability, low dielectric constants, and low water absorption rates.